Public participation and NGO activity in nature-based solutions in urban areas of China - Richard Hardiman; Anders Branth Pedersen; Anne Jensen; Kelly Guyu Dai; Carolyn Petersen (Nature-Based Solutions)
This paper analyses the degree and types of public participation in Nature-Based Solutions (NBS) projects in China. The paper is based upon the premise that NBS affect multiple aspects of the city as a place for the daily lives and activities of citizens and that NBS implementation can benefit from citizen and stakeholder involvement. NBS thus offer a platform for stimulating engagement between the local government and the public. Case studies are examined through a literature review, site visits, and interviews with researchers, local officials and NGOs in China. The paper indicates that there has been significant progress since the 1990s in formal requirements of public participation through Chinese legislation promoting the inclusiveness of the public in environmental and NBS decision-making, and acknowledgment of the importance of NGOs, however actual implementation of soliciting public opinion and involvement in NBS project design has been more limited. The case studies suggest that the level of involvement of the public in NBS activities and decision-making is the reciprocal of the size of the project, where there is a high-level of involvement in the smaller local projects, but minimal involvement in larger-scale NBS projects. We find that Public Private Partnerships (PPPs) have a significant potential to help finance NBS projects providing the project can forecast low risk and positive revenue for investors, therefore this model would merit further exploration. However, PPPs may also involve limited public participation by citizens and stakeholders beyond private companies and may therefore require targeted efforts to address local communities’ needs and interests. Local people are the most important (and willing) actors and opinionators in projects that directly affect their lives, livelihoods and well-being. The findings highlight the important role of NGOs in promoting and facilitating public participation, and accompanying co-benefits, in several of the Chinese case studies. Our study also suggests that symbiosis between local governments and the citizens could be invoked by local community-based organisations (e.g. Community Resident Committees or similar) that can act as a liaison point and catalyst to public participation in NBS projects, although significant training would also be required.